Self-assembled core–shell nanocomposite catalysts consisting of single-site Co-coordinated g-C3N4 and Au nanorods for plasmon-enhanced CO2 reduction. Issue 52 (October 2021) - Yoshii, Takeharu; Tamaki, Kenjirou; Kuwahara, Yasutaka; Mori, Kohsuke; Yamashita, Hiromi
Graphical abstract: Highlights: Core–shell-structured nanocomposite photocatalysts were designed and synthesized. Single-site Co species were immobilized into g-C3 N4 via a simple pyrolysis process. Co-doped g-C3 N4 coats the surface of Au nanorods via electrostatic self-assembly. Surface plasmon resonance of Au promoted CO production on single-site Co species. The core–shell structure is key to achieving high activity in the plasmonic catalysis. Abstract: Designing efficient photocatalyst materials for CO2 reduction and utilization has become important to address environmental and energy concerns. A new type of core–shell-structured nanocomposite catalyst is reported herein, in which single-site Co catalytic species are immobilized in graphitic carbon nitride (g-C3 N4 ) layered on Au nanorods (NRs) for surface plasmon resonance (SPR)-enhanced photocatalytic CO2 conversion. Single-site Co species were incorporated into g-C3 N4 via a simple pyrolysis process, and core–shell nanocomposites were self-formed via electrostatic interactions between the positively charged surfaces of the Au NRs and negatively charged single-site Co-coordinated g-C3 N4 layer. The structure was comprehensively examined by TEM, XRD, UV–vis, Co K-edge XAFS, FT-IR, and zeta potential measurements, which showed that the g-C3 N4 layer did not prevent the Au NRs from absorbing visible light. The nanocomposite efficiently catalyzed the reduction of CO2 to CO under visible light irradiation with the assistance of the SPR of the Au NRs. The catalytic activity of the core–shell-structured catalyst was superior to that of the corresponding aggregated catalyst, demonstrating that the formation of a core–shell structure affords efficient electron transport from the Au NRs to the catalytically active Co species.